Predicting the potential distribution of the endemic seabird Pelecanus thagus in the Humboldt Current Large Marine Ecosystem under different climate change scenarios - Jaime A. Cursach; Aldo Arriagada; Jaime R. Rau; Jaime Ojeda; Gustavo Bizama; Anderson Becerra (PeerJ, 2019)
Background The effects of global climate change on species inhabiting marine ecosystems are of growing concern, especially for endemic species that are sensitive due to restricted distribution. One method employed for determining the effects of climate change on the distribution of these organisms is species distribution modeling. Methods We generated a model to evaluate the potential geographic distribution and breeding distribution of the Peruvian pelican (Pelecanus thagus). Based on maximum entropy modeling (MaxEnt), we identified the environmental factors that currently affect its geographic distribution and breeding. Then we predicted its future distribution range under two climate change scenarios: moderate (rcp 2.6) and severe (rcp 8.5). Results The mean daytime temperature range and marine primary productivity explain the current potential distribution and breeding of the pelican. Under the future climate change scenarios, the spatial distribution of the pelican is predicted to slightly change. While the breeding distribution of the pelican can benefit in the moderate scenario, it is predicted to decrease (near −20 %) in the severe scenario. Discussion The current potential geographic distribution of the pelican is influenced to a large extent by thermal conditions and primary productivity. Under the moderate scenario, a slight increase in pelican breeding distribution is predicted. This increase in habitable area is explained by the climatic conditions in southern Chile, and those climatic conditions will likely be similar to the current conditions of the central coast of Chile. We predict that the coasts of southern Chile will constitute an important refuge for the conservation of the Peruvian pelican under future climate change scenarios.